CRIMINOLOGICAL REVIEW OF PERPETRATORS OF CHILD MOLESTERY IN CONNECTION WITH DIFFERENTIAL ASSOCIATION THEORY (Case Study at Class IIA Karawang Prison) - Kartika Salu, Vera; G, Deny; Abas, Mhd (Universitas Muhammadiyah Sumatera Utara, 2025)
Sexual abuse is inappropriate and unethical behaviour that violates norms of decency and morality, especially those related to sexual acts against others without consent or with the aim of degrading someone's dignity. This research aims to examine the behaviour of child molesters from the perspective of psychological criminology, with an emphasis on the application of Differential Association theory. In addition, this study also wants to explore the factors that encourage a person to commit child abuse, as well as how the countermeasures made by the Correctional Institution against the perpetrators. The approach used is qualitative with empirical juridical method, involving child molesters who have served their sentences at the Karawang Class IIA Correctional Institution. Data were obtained through interviews with perpetrators and prison officers. The results showed that some of the perpetrators had a background as victims of sexual violence, and grew up in an educational environment that tended to be permissive of such deviant behaviour. These conditions shape the tendency of deviant sexual behaviour. This finding supports the Differential Association theory, which states that criminal behaviour is not something that is brought from birth, but rather the result of the learning process in a particular social environment.